118 'One size doesn't fit all': Tailoring support for young people with long-term conditions. (22nd November 2019) - Nightingale, Ruth; McHugh, Gretl; Swallow, Veronica; Kirk, Susan
Abstract : Background: The responsibility for managing a long-term condition such as chronic kidney disease (CKD) typically transfers from parents to their child during adolescence. However, due to difficulties with self-managing their condition, some young people with CKD can experience poor health outcomes. Little is known about how health-care professionals (HCPs) can support the parent-to-child transfer of self-management responsibility, therefore this study aimed to explore the HCPs' role during this process. Methods: Twenty HCPs from two paediatric renal multidisciplinary teams participated in ten individual interviews and two focus groups. A grounded theory approach was used to collect, code and analyse data. Results: HCPs believed they have a responsibility to support young people with CKD to become involved in their health-care and acknowledged that their roles and relationships with families adjusted as self-management responsibility shifted from parent to child. Though national transition frameworks and local service provision guided their work, HCPs stressed the need to make individualised judgements around a young person's readiness to become more involved in their health-care. Strategies used to support the handover of responsibility included working collaboratively with families, using technology and balancing 'typical' adolescent behaviour with maintaining health. There was uncertainty around whether including or excluding parents from appointments supported the transfer process; however, there was recognition that parents potentially needed more support with relinquishing responsibility to their child. Peer support, mentorship and role models were identified as areas for potential development that could benefit both young people to take charge of their health-care and parents to 'let go'. Conclusion: Support for families with the parent-to-child transfer of self-management needs to be individualised and take into account both the young person's and parent's preferences and needs. Further research is needed to develop and test interventions that could support families with this process.